Correlation of whole blood hydroxychloroquine concentration with cutaneous lupus erythematosus and factors associated with it: first multicenter, cross-sectional analysis in Malaysia - Peh, D.; Wan Ahmad Kammal, W. S. L.; Beh, P. J.; Yong, A. C. H.; Tan, W. C.; Lim, A. L.; Thevarajah, S.; Stanslas, J.; How, Kang Nien (Wiley-Blackwell Publishing, 2022)
Hydroxychloroquine (HCQ) is the first-line systemic treatment for cutaneous lupus erythematosus (CLE). Whole blood HCQ concentration (WBHCQ) was found to correlate with CLE severity among Caucasians. However, studies on Asians are scarce. We aim to explore the relationship of WBHCQ with CLE disease activity among multi-racial Malaysians and the factors associated with WBHCQ. A cross-sectional study targeting patients with CLE was conducted from 1 June till 30 November 2019. Disease activity was assessed using Cutaneous Lupus Erythematosus Disease Area and Severity Index – Activity Score (CLASI-AS). Blood was analyzed for WBHCQ concentration using a high-performance liquid chromatography technique. Statistical analysis was done using R studio version 1.2.1335. A total of 88 subjects (male : female, 4.5:1) with a median age of 41 years old were recruited. The median duration CLE was 5 years. The majority had acute cutaneous lupus (n = 45, 51.1%). The median WBHCQ was 946.8 ng/mL. Indians were found to have the highest WBHCQ (median ± interquartile range [IQR], 1515.4 ± 1494.8 ng/mL). Males had a lower WBHCQ (median ± IQR, 733.5 ± 573.8 ng/mL) than females (995.5 ± 925.1 ng/mL). However, no statistically significant association between race and sex with WBHCQ was demonstrable (p = 0.247, p = 0.066). No correlation was demonstrated between WBHCQ and CLASI-AS (r = −0.02, p = 0.851). A positive correlation was found between HCQ dosage (ideal bodyweight) and WBHCQ (r = 0.24, p = 0.027). No other factors were found associated with WBHCQ. Indians and females were observed to have higher WBCHQ; however, no significant correlation was identified. Further study is required to confirm the finding.